Tondano watershed and Plastic Waste Elimination Activities - Henneke Pangkey; Hariyani Sambali (Sam Ratulangi University, 2021)
The role of Tondano watershed is very important for the people of North Sulawesi. It can be said as the heart of the economy for the people who live suround it. One of them is the existence of aquaculture business activities in the form of fixed cage. It was found that Tondano watershed has shown an alarming decline in function. There are several causes, one of which is the increasing volume of plastic waste. The house wife group is important in its role in maintaining the sustainability of Tondano watershed. This group is believed to be one of the leaders for removing plastic waste in Tondano watershed.Keyword: Tondano watershed, plastic waste, housewife group, sustainability ABSTRAKWilayah DAS Tondano sangat penting peranannya bagi masyarakat Sulawesi Utara.Â Dapat dikatakan sebagai jantungnya perekonomian bagi masyarakat yang hidup di sekitarnya.Â Salah satu di antaranya adalah adanya kegiatan usaha akuakultur dalam bentuk karamba jaring tancap. Ditemukan fungsi DAS Tondano telah menunjukkan adanya penurunan yang mengkuatirkan. Ada beberapa penyebab, salah satunya adalah meningkatnya volume limbah plastik. Kelompok ibu RT penting dalam perannya menjaga keberlanjutan DAS Tondano.Â Kelompok ini dipercaya dapat menjadi salah satu ujung tombak untuk mengentas limbah plastik di DAS Tondano.Keyword: DAS Tondano, limbah plastik, kelompok ibu RT, keberlanjutan